Feministic Analysis of Arundhati Roy's the God of Small Things in the Light of Post Colonialism - Zaheri, Shiva; Moosavinia, Sayyed Rahim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This paper attempts to analyze the mentioned novel based on postcolonial studies in Arundhati Roy's The God of Small Things.Â  The concepts that can be mentioned in this novel are history, diaspora, hybridity, the role of women in Indian society, globalization, resistance and orientalism. These concepts are used from postcolonial theorists, Edward W. Said and Homi K. Bhabha.Prominent issue is the role women in Indian society, because there are several female characters, such as Ammu, Rahel, and so on in TGST. Economic growth causes change in Ayemenem. It becomes a globalized community. Postcolonial resistance is an important issue in the novel. When Roy uses English language which it is a colonial language, she does a kind of resistance against colonization itself. Roy refers to the childrenâ€™s life as a means of resistance.